Cardiometabolic Risk in Acromegaly: A Review With a Focus on Pasireotide - Puglisi, Soraya; Ferraù, Francesco; Ragonese, Marta; Spagnolo, Federica; Cannavò, Salvatore (Frontiers in Endocrinology, 2020)
Acromegaly is a disease due to chronic GH excess and a consequent rise in IGF-1 levels. This rare endocrine condition is associated with metabolic alterations such as hyperglycaemia, dyslipidaemia, and systemic arterial hypertension, which, in addition to GH excess-related cardiovascular changes, play critical roles in increasing cardiovascular risk and mortality rates. Biochemical control of acromegaly, achieved by means of surgical, and/or medical treatment, positively impacts on cardiovascular risk factors and metabolic alterations, reducing overall patient mortality. However, treatment modalities of acromegaly and disease control differently impact on glucose homeostasis and lipid changes, and consequently on cardiometabolic risk. In this regard, pasireotide was shown to significantly influence glucose metabolism. This review summarizes the cardiometabolic consequences of acromegaly and its treatment, focusing on available data around the effects of medical therapy with pasireotide on factors that influence cardiometabolic risk.